Pandemic influenza A/H1N1 (sw2009) in Russia: epidemiology, diagnosis, clinical picture, and treatment - Svetlana Borisovna Yatsyshina; Andrey Nikolaevich Minenko; Tat'yanaya Evgen'evna Kushakova; Mariya Nikolaevna Praded; Anna Viktorovna Kudryavtseva; German Aleksandrovich Shipulin; Viktor Vasil'evich Maleev; V I Pokrovskiy; S B Yatsyshina; A N Minenko; T E Kushakova; M N Praded; et al. (Терапевтический архив, 2010)
Aim. To study the epidemiological and clinical features of the 2009-2010 pandemic influenza in Russia. Subjects and methods. Materials from 874 patients, including postmortem samples from 287 subjects, were examined applying the AmpliSens Influenza virus A/H1-swine-FL PCR kit designed and produced by the Central Research Institute of Epidemiology. The clinical and postmortem characteristics of 68 patients who had died from influenza A/H1N1 (sw2009) were analyzed in detail. Results. The cause of deaths was primary virus pneumonia in most cases. The major manifestation of viral pathogenicity was impaired microcirculation leading to hemorrhage. No mutations conferring resistance to oseltamivir and arbidol were found. All A/H1N1swl viruses had genetic markers of remantadin resistance. Conclusion. The reagent kits developed by the Central Research Institute of Epidemiology proved to be effective. It is necessary to set up PCR laboratories that differentially diagnose influenza and acute respiratory viral infections in health care facilities in order to make early laboratory diagnosis of influenza and to timely perform its specific therapy.